Selected determinants of occupational stress and burnout in physiotherapists and IT professionals - Dariusz Mikołajewski; Jolanta Masiak; Emilia Mikołajewska (Journal of Education, Health and Sport, 2023)
Introduction Occupational stress and burnout have a statistically significant negative impact on learning and work in the professional groups studied, but the exact manner and strength of the impact and the neurophysiological mechanisms underlying the aforementioned phenomena are not yet well understood. The main reason for this is the paucity of research, both on the neurobiological basis and on the incidence and impact on the lives of different professional groups.